Evaluation of wheat genotypes for farinographic characteristics in relation to their chapati-making properties - Kumar, Satish; Sohu, Virinder Singh; Singh, Rajinder Pal; Srivastava, Puja; Sharma, Indu; Bains, Navtej Singh (Journal of Cereal Research, 2013)
A set of 34 wheat genotypes were evaluated over two seasons for chapati making properties and Farinographic characteristics. The genotypes used in the study included tall Indian landraces, released varieties known to have good quality, genetic stocks possessing one or other quality components and high yielding commercial varieties. The results indicated that superior chapati quality wheats scored low for almost all the farinographic characteristics thus negative correlation as observed in one or the other season. Consistent trends were notobserved possibly due to change in set constituents and differential environments.